Preparation method and application of MOF composite aerogel based on cellulose in-situ growth
By synthesizing MOF on cellulose in situ under low temperature aqueous phase conditions, the problem of insufficient agglomeration and adsorption performance of MOF materials in the prior art was solved, and a composite aerogel based on cellulose with high adsorption properties was prepared. , realizes efficient adsorption of metal ions such as vanadium, molybdenum, and nickel.
Patent Information
- Application Number
- CN202411694860.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-07
AI Technical Summary
There are problems with organic solvents and high temperature and high pressure environments during the existing in-situ synthesis of MOFs, which leads to the agglomeration of MOF materials, and the porosity and particle size are uneven, affecting the adsorption performance.
Under low-temperature aqueous phase conditions, cellulose and MOF growth solution were added to water to synthesize MOF in situ, and a composite aerogel based on cellulose was prepared, which solved the problem of insufficient agglomeration and adsorption performance of MOF materials.
By synthesizing MOF in situ on cellulose, good porosity and particle size uniformity are obtained, adsorption performance is improved, and it has strong affinity with water, and can effectively adsorb metal ions such as vanadium, molybdenum, and nickel.
Smart Images

Figure CN119386835A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a preparation method and application of MOF composite aerogel based on in-situ growth of cellulose. Background Art
[0002] With the rapid advancement of industrialization, a large amount of industrial wastewater is discharged into water bodies. These wastewaters contain harmful components such as heavy metals, organic matter, acid and alkali substances, which seriously pollute the water bodies. At present, the methods used for water pollution treatment are mainly: chemical precipitation method, chemical agents and metal ions form precipitation, and then are removed by filtration; electrosorption method, which works on the basis of anode reaction technology to degrade metal ions in sewage; biological method, using microorganisms or plants to degrade metal ions in water; adsorption method, this sewage treatment method uses physical and chemical methods to adsorb various impurities in sewage. At present, chemical precipitation method is widely used, but this method consumes a lot of chemical agents and may generate other substances to cause secondary pollution to the environment. As an environmentally friendly method, adsorption method has many advantages. The adsorbents used in adsorption method, such as activated carbon, can be regenerated or recycled by appropriate methods after reaching saturation, reducing secondary pollution to the environment.
[0003] The development of adsorbent materials should focus on their ecological and environmental protection. Biomass is an easily available and environmentally friendly material. Orange peel contains a large amount of cellulose and a small amount of lignin, hemicellulose, pectin, pigments and other natural polymers. The hydroxyl, carboxyl and amino groups contained in the composition can be used to adsorb heavy metals.
[0004] Cellulose is a linear polysaccharide and one of the most abundant polymers on earth. Natural cellulose can be extracted from biomass materials such as cotton, flax, wood and orange peel, which are biodegradable, biocompatible and inexpensive. Despite this, they still face some challenges in practical applications, such as weak mechanical properties and low porosity. In order to give cellulose materials more functions, traditional methods such as physical adsorption and chemical surface modification have been widely used. Natural cellulose fiber-based materials are widely used in daily life due to their easy availability, environmental protection, good processability and excellent physical and mechanical properties. Surface modification of natural fibers using nanostructured materials is one of the effective strategies to achieve cellulose-based multifunctional integration.
[0005] MOFs materials are porous crystalline materials composed of metal ions or metal clusters coordinated with organic ligands. MOFs materials have very high specific surface area and adjustable pore size, which makes them have broad application prospects in gas storage, gas separation, adsorption and drug release. The pore size and structure of MOFs materials can be designed and regulated to enable them to selectively adsorb specific substances. This makes MOFs materials highly selective for adsorption separation and can achieve efficient separation of different gases, liquids or ions.
[0006] There are two main ways to combine MOF materials with cellulose. One is the direct loading method, which is to pre-synthesize MOF materials and add them to the cellulose precursor solution. The advantage of this method is that it is easy to operate, but MOF materials are prone to agglomeration. The second is the in-situ growth method, which is to grow MOF on cellulose in situ by immersing cellulose in a solution containing organic ligands and metal ions. The advantage of this method is that it reduces the amount of synthetic MOF materials and reduces the degree of MOF aggregation, but MOF is usually difficult to grow on the surface, so it is often grown under high temperature and high pressure. Summary of the invention
[0007] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing a composite aerogel based on in-situ growth of MOF by cellulose, which solves the problems of organic solvents and high temperature and high pressure environment in the existing in-situ synthesis of MOF process, and prepares a composite aerogel based on in-situ growth of MOF by adding cellulose and MOF growth liquid into water to synthesize MOF in-situ at low temperature;
[0008] The present invention also provides the use of the cellulose-based in-situ grown MOF composite aerogel in the adsorption of vanadium, molybdenum and nickel metal ions.
[0009] The objective of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a MOF composite aerogel based on in-situ growth of cellulose comprises the following steps:
[0011] Step 1: Add orange peel powder to NaOH solution for heating and mechanical stirring, then add the washed and dried powder to a mixed solution of TEMPO, NaBr and NaClO for mechanical stirring, then wash and dry to obtain cellulose powder;
[0012] Step 2: Mix cellulose powder and dimethylimidazole, add them into deionized water and stir them mechanically to obtain a mixed solution A;
[0013] Step 3: gradually adding cobalt nitrate and zinc chloride to the mixed solution A obtained in step 2 and stirring evenly, then heating, mechanically stirring for a certain period of time, cooling, adding polyethyleneimine (PEI) and mechanically stirring evenly to obtain a mixed solution B;
[0014] Step 4: dripping the cross-linking solution dropwise into the mixed solution B to perform a cross-linking reaction to obtain a composite hydrogel;
[0015] Step 5: After sealing, heating and baking the composite hydrogel, washing with deionized water and drying to obtain the composite aerogel.
[0016] In some specific embodiments, the concentration of the NaOH solution in step 1 is 0.1-0.5 mol / L, the ratio of the orange peel powder to the NaOH solution is 1 g:(30-50) ml; and the ratio of the cellulose powder, TEMPO, NaBr and NaClO solution is (5-15) g:(0.3-0.5) g:(0.2-0.4) g:(10-20) ml.
[0017] In certain specific embodiments, in step 2, the ratio of the cellulose powder to dimethylimidazole in step 2 is (400-600) mg: (0.5-0.8) mmol.
[0018] In certain specific embodiments, the ratio of cobalt nitrate, zinc chloride and polyethyleneimine in step 3 is (0.1-0.4) mmol: (0.1-0.4) mmol: (1-3) g, and the interval between the addition of cobalt nitrate and zinc chloride is 3-8 min.
[0020] In some specific embodiments, the speed of the mechanical stirring in step 3 is 1000 r / min to 2000 r / min, the time is 2-3 h, and the heating temperature is 80-90°C.
[0021] In some specific embodiments, the rotation speed of the mechanical stirring in step 2 is 1000 r / min to 2000 r / min, and the time is 20-40 min.
[0022] In some specific embodiments, the cross-linking solution in step 4 is a 10 wt % epichlorohydrin (ECH) solution.
[0023] In some specific embodiments, the heating temperature described in step five is 50-70°C, and the time is 10-14h, and the drying includes pre-freezing and freeze-drying performed in sequence; the pre-freezing temperature is -20°C to -196°C, and the time is 0.5 to 6h; the freeze-drying temperature is -45°C to 40°C, the pressure is 2 to 50Pa, and the time is 6 to 48h.
[0024] A composite aerogel based on cellulose in-situ grown MOF prepared according to the above-mentioned preparation method.
[0025] An application of the aforementioned cellulose-based in-situ grown MOF composite aerogel in the field of metal ion adsorption.
[0026] Furthermore, the cellulose-based in-situ grown MOF composite aerogel is used in the simultaneous adsorption of vanadium, molybdenum and nickel metal ions.
[0027] Compared with the prior art, the present invention has at least the following advantages:
[0028] 1) The preparation method provided by the present invention obtains a composite aerogel containing MOF material by in-situ synthesizing MOF on cellulose under low-temperature aqueous phase conditions. The MOF material synthesized in situ on cellulose has good porosity and particle size, and is evenly covered on the cellulose, thereby avoiding the loss of active components and solving the problem of easy agglomeration of MOF materials. At the same time, it also effectively improves the adsorption performance and has good affinity with water, enabling the surface to simultaneously achieve the adsorption of three metal ions of vanadium, molybdenum and nickel.
[0029] 2) The preparation method of the MOF composite aerogel based on in situ growth of cellulose provided in the present application is simple, the raw materials are readily available, the reaction process is mild, and the prepared adsorbent is suitable for the removal of metal ions, and has a good development prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0031] Figure 1 The SEM images of the composite aerogel prepared in Example 3 of the present invention at different magnifications;
[0032] Figure 2 The adsorption performance of the composite aerogels prepared with different Co:Zn addition ratios in Examples 1-4 on vanadium, molybdenum and nickel metal ions;
[0033] Figure 3 The adsorption performance of the adsorption materials prepared in Example 3 and Comparative Examples 1-5 for vanadium, molybdenum and nickel metal ions. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0035] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0036] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.
[0037] Example 1
[0038] The preparation method of MOF composite aerogel based on in-situ growth of cellulose provided in this embodiment comprises the following steps:
[0039] 1) adding 10 g of orange peel powder to 400 mL of 0.2 mol / L NaOH solution, heating and mechanically stirring, then washing and drying, adding to a mixed solution of 0.4 g of TEMPO (2,2,6,6-tetramethylpiperidinyl oxide), 0.25 g of NaBr and 15 mL of 12% NaClO, mechanically stirring, then washing and drying to obtain cellulose powder;
[0040] 2) 500 mg of cellulose powder was mixed in 20 mL of deionized water and stirred evenly, followed by adding 0.6 mmol of dimethylimidazole and stirring at a speed of 1500 r / min for 30 min to obtain a mixed solution A;
[0041] 3) Add 0.1 mmol of cobalt nitrate to the mixed solution A and stir for 5 min, then add 0.1 mmol of zinc chloride and stir for 5 min; then transfer to a water bath and heat at 90°C, stir at 1500 r / min for 2 h, cool to room temperature, add 2 g of polyethyleneimine and stir evenly to obtain a mixed solution B;
[0042] 4) adding 10 wt % ethylene oxide propylene cross-linking solution (1.2 ml) dropwise into the mixed solution to carry out a cross-linking reaction, and mechanically stirring at a speed of 1500 r / min for 30 min to obtain a composite hydrogel;
[0043] 5) The composite hydrogel was sealed and heated and baked (heating temperature was 60°C for 12 hours), then washed with deionized water, and then pre-frozen at -20°C for 2 hours and freeze-dried at an air pressure of 5 Pa and a temperature of -40°C for 48 hours to obtain a composite aerogel.
[0044] Example 2
[0045] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this embodiment is basically the same as that in Example 1, except that the molar amounts of cobalt nitrate and zinc chloride in step 3) are both 0.2 mol, specifically:
[0046] 3) Add 0.2 mmol of cobalt nitrate to the mixed solution A and stir for 5 min, then add 0.2 mmol of zinc chloride and stir for 5 min, then transfer to a water bath and heat at 90° C., stir at 1500 r / min for 2 h, cool to room temperature, add 2 g of polyethyleneimine and stir evenly to obtain a mixed solution B;
[0047] Example 3
[0048] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this embodiment is basically the same as that in Example 1, except that the molar amounts of cobalt nitrate and zinc chloride in step 3) are both 0.3 mol, specifically:
[0049] 3) Add 0.3 mmol of cobalt nitrate to the mixed solution A and stir for 5 min, then add 0.3 mmol of zinc chloride and stir for 5 min, then transfer to a water bath and heat at 90° C., stir at 1500 r / min for 2 h, cool to room temperature, add 2 g of polyethyleneimine and stir evenly to obtain a mixed solution B;
[0050] Example 4
[0051] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this embodiment is basically the same as that in Example 1, except that the molar amounts of cobalt nitrate and zinc chloride in step 3) are both 0.4 mol, specifically:
[0052] 3) Add 0.4 mmol of cobalt nitrate to the mixed solution A and stir for 5 min, then add 0.4 mmol of zinc chloride and stir for 5 min, then transfer to a water bath and heat at 90° C., stir at 1500 r / min for 2 h, cool to room temperature, add 2 g of polyethyleneimine and stir evenly to obtain a mixed solution B;
[0053] Performance Test:
[0054] The present application conducts a performance test on the four composite aerogels with different metal ion addition contents prepared in Examples 1-4. The specific steps of the experiment are as follows:
[0055] Prepare 50mL of vanadium, molybdenum and nickel solutions. The pH of the vanadium and molybdenum solutions is 3, and the solution concentration is 250mg / L. The pH of the nickel solution is 7, and the solution concentration is 100mg / L. Add the adsorbent and stir the solution on a magnetic stirrer. The amount of adsorbent is 20mg. The experimental temperature is 25±3℃. The test results are shown in Table 1:
[0056] Table 1: Performance test of composite aerogel
[0057] Co:Zn addition ratio (mmol:mmol) 0.1:0.1 0.2:0.2 0.3:0.3 0.4:0.4 Vanadium ion adsorption capacity (mg / g) 240.8 460.85 496.86 494.66 Molybdenum ion adsorption capacity (mg / g) 392.02 488.99 493.61 432.23 Nickel ion adsorption capacity (mg / g) 113.98 248.75 249.38 139.5
[0058] As can be seen from Table 1, the composite aerogel in the present application has good adsorption performance for vanadium, molybdenum and nickel metal ions when the Co:Zn metal ion addition ratio is 0.3:0.3.
[0059] Comparative Example 1
[0060] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this comparative example comprises the following steps:
[0061] 1) Add 0.6 mmol of dimethylimidazole to 20 mL of deionized water and stir at 1500 r / min for 30 min;
[0062] 2) Add 0.3 mmol cobalt nitrate and stir for 5 min, then add 0.3 mmol zinc chloride and stir for 5 min, then transfer to a water bath and heat at 90°C, stir at 1500 r / min for 2 h, and then cool to room temperature;
[0063] 3) After centrifugation and washing with ethanol and water, the solution was dried in an oven at 60°C to obtain ZIF-67@ZIF-8 powder.
[0064] Comparative Example 2
[0065] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this comparative example comprises the following steps:
[0066] 1) adding 10 g of orange peel powder to 400 mL of 0.2 mol / L NaOH solution and heating and mechanically stirring, then adding the washed and dried powder to a mixed solution of 0.4 g of TEMPO, 0.25 g of NaBr and 15 mL of 12% NaClO and mechanically stirring, then washing and drying to obtain cellulose powder;
[0067] 2) 500 mg of cellulose powder was added to 20 mL of deionized water and stirred at a speed of 1500 r / min to obtain a mixed solution;
[0068] 3) The mixed solution was transferred to a water bath and heated at 90°C, stirred at 1500 r / min for 2 h, cooled to room temperature, and 2 g of polyethyleneimine was added and stirred to obtain a mixed solution;
[0069] 4) adding 10 wt % ethylene oxide propylene cross-linking solution (1.2 ml) dropwise into the mixed solution to carry out a cross-linking reaction, and mechanically stirring at a speed of 1500 r / min for 30 min to obtain a composite hydrogel;
[0070] 5) The composite hydrogel was sealed and heated and baked (heating temperature was 60°C for 12 hours), then washed with deionized water, pre-frozen at -20°C for 2 hours, and then freeze-dried at -40°C for 48 hours to obtain a composite aerogel (CPE), and the freeze-drying pressure was 5 Pa.
[0071] Comparative Example 3
[0072] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this comparative example comprises the following steps:
[0073] 1) Add 2 g of polyethyleneimine into 20 mL of deionized water and stir to obtain a mixed solution;
[0074] 2) adding 10 wt % ethylene oxide propylene cross-linking solution (1.2 ml) dropwise into the mixed solution to carry out a cross-linking reaction, and mechanically stirring at a speed of 1500 r / min for 30 min to obtain a composite hydrogel;
[0075] 3) The composite hydrogel was sealed and heated and baked (heating temperature was 60°C for 12 hours), then washed with deionized water, pre-frozen at -20°C for 2 hours, and then freeze-dried at -40°C for 48 hours to obtain a composite aerogel (PE), and the freeze-drying pressure was 5 Pa.
[0076] Comparative Example 4
[0077] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this comparative example comprises the following steps:
[0078] 1) adding 10 g of orange peel powder to 400 mL of 0.2 mol / L NaOH solution and heating and mechanically stirring, then adding the washed and dried powder to a mixed solution of 0.4 g of TEMPO, 0.25 g of NaBr and 15 mL of 12% NaClO and mechanically stirring, then washing and drying to obtain cellulose powder;
[0079] 2) 500 mg of cellulose powder was mixed in 20 mL of deionized water and stirred evenly, then 500 mg of ZIF-67@ZIF-8 powder was added and stirred evenly, and then the mixture was transferred to a water bath and heated at 90° C. and stirred at 1500 r / min for 2 h. After cooling to room temperature, 2 g of polyethyleneimine was added and stirred evenly to obtain a mixed solution;
[0080] 3) adding 10 wt % ethylene oxide propylene cross-linking solution (1.2 ml) dropwise into the mixed solution to carry out a cross-linking reaction, and mechanically stirring at a speed of 1500 r / min for 30 min to obtain a composite hydrogel;
[0081] 4) The composite hydrogel was sealed and heated and baked (heating temperature was 60°C for 12 h), then washed with deionized water, pre-frozen at -20°C for 2 h, and then freeze-dried at -40°C for 48 h to obtain a composite aerogel (CPE / ZIF-67@ZIF-8), and the freeze-drying pressure was 5 Pa.
[0082] Comparative Example 5
[0083] The preparation method of the MOF composite aerogel based on in-situ growth of cellulose provided in this comparative example comprises the following steps:
[0084] 1) adding 10 g of orange peel powder to 400 mL of 0.2 mol / L NaOH solution and heating and mechanically stirring, then adding the washed and dried powder to a mixed solution of 0.4 g of TEMPO (2,2,6,6-tetramethylpiperidinyl oxide), 0.25 g of NaBr and 15 mL of 12% NaClO and mechanically stirring, then washing and drying to obtain cellulose powder;
[0085] 2) 500 mg of cellulose powder was mixed in 20 mL of deionized water and stirred evenly, followed by adding 0.6 mmol of dimethylimidazole and stirring at a speed of 1500 r / min for 30 min to obtain a mixed solution;
[0086] 3) Add 0.3 mmol of cobalt nitrate to the mixed solution and stir for 5 min, then add 0.3 mmol of zinc chloride and stir for 5 min, then transfer to a water bath and heat at 90°C for 2 h and cool to room temperature;
[0087] 4) adding 10 wt % ethylene oxide propylene cross-linking solution (1.2 ml) dropwise into the mixed solution to carry out a cross-linking reaction, and mechanically stirring at a speed of 1500 r / min for 30 min to obtain a composite hydrogel;
[0088] 5) The composite hydrogel was sealed and heated and baked (heating temperature was 60°C for 12 h), then washed with deionized water, pre-frozen at -20°C for 2 h, and then freeze-dried at -40°C for 48 h to obtain a composite aerogel (CE-ZIF-67@ZIF-8), and the freeze-drying pressure was 5 Pa.
[0089] The present application performs a performance test on the adsorption material obtained in Comparative Examples 1-5. The specific steps of the experiment are as follows: 50 mL of vanadium, molybdenum and nickel solutions are prepared. The pH of the vanadium and molybdenum solutions is 3, and the solution concentration is 250 mg / L. The pH of the nickel solution is 7, and the solution concentration is 100 mg / L. The adsorbent is added and the solution is placed on a magnetic stirrer for stirring. The amount of the adsorbent is 20 mg. The experimental temperature is 25±3° C. The test results are shown in Table 2:
[0090] Table 2: Performance test of different adsorption materials
[0091]
[0092]
[0093] From the data in Table 2, it can be seen that by comparing the data of Comparative Example 1 (ZIF-67@ZIF-8), Comparative Example 2 (CPE) and Example 3 (CPE-ZIF-67@ZIF-8), under the same preparation conditions, the directly synthesized MOF and the simply treated biomass have lower adsorption capacities for vanadium, molybdenum and nickel; Comparative Example 3 (PE) directly uses PEI to prepare the adsorbent, which has a certain improvement in the adsorption capacity for vanadium and molybdenum, but has an extremely low adsorption capacity for nickel; Comparative Example 4 (CPE / ZIF-67@ZIF-8) prepared MOF powder compared with Example 3 The adsorbent prepared by directly mixing the molybdenum with cellulose has a greatly improved adsorption capacity for vanadium, but has a lower adsorption capacity for molybdenum and nickel; Compared with Example 3, the adsorbent prepared in Comparative Example 5 (CE-ZIF-67@ZIF-8) without adding polyethyleneimine has a very high adsorption capacity for vanadium and molybdenum, and has a certain adsorption effect on nickel, but in the absence of polyethyleneimine, the mechanical properties of the adsorption material are low and difficult to recover; Example 3 is obtained by in-situ synthesizing MOF on cellulose and finally obtaining it through composite crosslinking, and has good adsorption performance for vanadium, molybdenum and nickel, and also has better mechanical properties.
[0094] In order to observe the composite aerogel intuitively, the morphology and microstructure of the composite aerogel were described using a scanning electron microscope. The distribution diagram of the composite aerogel at different magnifications of the scanning electron microscope image is shown in Figure 2. Figure 1As shown, it can be seen that the sample surface presents a cubic MOF structure and a three-dimensional network structure, while the interconnected skeleton structure constitutes countless pores. Such a physical and chemical cross-linked network is conducive to exposing numerous binding sites, and is also conducive to the mass transfer of metal ions and promotes the removal process.
[0095] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing MOF composite aerogel based on in-situ growth of cellulose, characterized in that: The following steps are involved: Step 1: Add orange peel powder to NaOH solution, heat and mechanically stir, then add the washed and dried powder to a mixed solution of TEMPO, NaBr and NaClO, mechanically stir, and then wash and dry to obtain cellulose powder; Step 2: Mix cellulose powder and dimethylimidazole, add them into deionized water and stir them mechanically to obtain a mixed solution A; Step 3: gradually adding cobalt nitrate and zinc chloride to the mixed solution A obtained in step 2 and stirring evenly, then heating, mechanically stirring for a certain period of time and then cooling, adding polyethyleneimine and mechanically stirring evenly to obtain a mixed solution B; Step 4: dripping the cross-linking solution into the mixed solution B drop by drop to perform a cross-linking reaction to obtain a composite hydrogel; Step 5: After sealing, heating and baking the composite hydrogel, washing with deionized water and drying to obtain the composite aerogel.
2. The method for preparing MOF composite aerogel based on in-situ growth of cellulose according to claim 1, characterized in that: The concentration of the NaOH solution in step 1 is 0.1-0.5 mol / L, the ratio of the orange peel powder to the NaOH solution is 1 g:(30-50) ml; and the ratio of the cellulose powder, TEMPO, NaBr and NaClO solution is (5-15) g:(0.3-0.5) g:(0.2-0.4) g:(10-20) ml.
3. The method for preparing MOF composite aerogel based on in-situ growth of cellulose according to claim 1, characterized in that: The ratio of the cellulose powder to dimethylimidazole in step 2 is (400-600) mg: (0.5-0.8) mmol.
4. The method for preparing MOF composite aerogel based on in-situ growth of cellulose according to claim 1, characterized in that: In step 3, the ratio of cobalt nitrate, zinc chloride and polyethyleneimine is (0.1-0.4) mmol: (0.1-0.4) mmol: (1-3) g, and the interval between the addition of cobalt nitrate and zinc chloride is 3-8 min.
5. The method for preparing MOF composite aerogel based on in-situ growth of cellulose according to claim 1, characterized in that: The speed of the mechanical stirring in step 3 is 1000r / min-2000r / min, the time is 2-3h, and the heating temperature is 80-90°C.
6. The method for preparing MOF composite aerogel based on in-situ growth of cellulose according to claim 1, characterized in that: The rotation speed of the mechanical stirring described in step 2 is 1000r / min~2000r / min, and the time is 20-40min.
7. The method for preparing MOF composite aerogel based on in-situ growth of cellulose according to claim 1, characterized in that: The cross-linking solution described in step 4 is a 10 wt % epichlorohydrin solution.
8. The method for preparing MOF composite aerogel based on in-situ growth of cellulose according to claim 1, characterized in that: The heating temperature described in step five is 50-70°C, and the time is 10-14h. The drying includes pre-freezing and freeze-drying performed in sequence; the pre-freezing temperature is -20°C to -196°C, and the time is 0.5 to 6h; the freeze-drying temperature is -45°C to 40°C, the pressure is 2 to 50Pa, and the time is 6 to 48h.
9. A composite aerogel based on cellulose in-situ grown MOF prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the cellulose-based in-situ grown MOF composite aerogel according to claim 9 in the field of metal ion adsorption.
Citation Information
Cited By
Magnetic particle loaded porous composite material for sewage treatment as well as preparation method and application thereof
CN120243140A
MOF in-situ growth regenerated cellulose aerogel fiber as well as preparation method and application thereof
CN121556166A
Nanocellulose composite aerogel as well as preparation method and application thereof
CN121652452A
Composite cellulose aerogel material as well as preparation method and application thereof
CN122183561A